Literature review analysis of aortitis induced by granulocyte-colony stimulating factor - Zhao, Ting; Xu, Huanhuan (Frontiers in Pharmacology, 2024)
BackgroundRecombinant human granulocyte-colony stimulating factors (G-CSF)-induced aortitis is a rare but particularly serious adverse event, commonly seen in cancer patients undergoing chemotherapy. The aim of this article is to clarify the clinical characteristics of G-CSF- induced aortitis and provide effective references for clinical diagnosis and intervention.MethodsCase reports of adverse reactions of aortitis induced by G-CSF were collected from the relevant databases. The patients’ basic information and adverse reaction process were recorded and subjected to descriptive analysis.ResultsA total of 72 patients were enrolled, including 14 males and 58 females, with a mean age of 61.83 ± 10.30 years. The G-CSF type with the highest frequency of occurrence of aortitis is pegfilgrastim. Apart from three healthy stem cell donors, G-CSF-induced aortitis was primarily found in patients with underlying malignancies, especially in patients with breast cancer. The most common anticancer drugs used at onset were docetaxel, cyclophosphamide, and doxorubicin. CT scan showed that aortitis most commonly occured in the aortic arch and its branches. Most patients had a good prognosis, but 3 cases developed complications. Importantly, G-CSF-induced aortitis was also found in 4 asymptomatic patients.ConclusionThis article found that G-CSF-induced aortitis not only occured in cancer patients undergoing chemotherapy as previously reported in literature, but also in healthy stem cell donors. Especially, asymptomatic patients with G-CSF-induced aortitis faced a greater risk of being missed by the attending physician.